Symposium 5: The Paradox of Social Media and Higher Education Institutions - Bonzo, Justin; Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2010)
This paper explores the paradox that occurs between institutional expectations and expectations held by student regarding the use of social media in support of learning in higher education settings. Specifically, the example is given of a disagreement that took place in a recent conversation in a distributed medical education programme in Canada. The current body of research regarding the incongruity of expectations about integrating social media into a higher education institution framework suggests that a widening gap is emerging and that conflict is taking place. The example from Canada exemplifies the difference that exists in people’s understandings and expectations of how social media can be employed for benefit in education. The paper looks at the principles of social media and the potential impact on many of society’s institutions, including government, commerce, media and education. Interestingly, higher education seems to have fallen behind in adopting and adapting to the new social media reality. The key points of social constructivist thinking are then examined with special attention to the following five points: learning requires active participation by the learner; previous experience is important when reinforcing new learning; individual knowledge construction requires a social interaction element; negotiation within the learning environment is essential; and, learning best takes place within a socio-cultural context. These principles are then addressed in relation to the social media principles of active participation, collaboration and that of reflection. Finally, three points are expanded as to potential sources and reasons why conflict may occur when trying to integrate a popular social media perspective into the established higher education setting. These are: existing hierarchical structure of higher education institutions; accreditation and quality concerns; and, formal and informal learning. Social media is more than computer application and programs and the technology behind them it is about transformation. At its core, social media is a collection of ideas about community, openness, flexibility, collaboration, transformation and it is all user-centred. If education and educational institutions can understand and adopt these principles, perhaps there is a chance for significant change in how we teach and learn in formal and informal settings. The challenge is to discover how to facilitate this change.